2018
DOI: 10.1186/s12859-018-2184-4
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing histopathologic deep learning classification and anomaly detection using nonlinear feature space dimensionality reduction

Abstract: BackgroundThere is growing interest in utilizing artificial intelligence, and particularly deep learning, for computer vision in histopathology. While accumulating studies highlight expert-level performance of convolutional neural networks (CNNs) on focused classification tasks, most studies rely on probability distribution scores with empirically defined cutoff values based on post-hoc analysis. More generalizable tools that allow humans to visualize histology-based deep learning inferences and decision makin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 21 publications
3
35
0
Order By: Relevance
“…Recently, there has been a surge of interest in developing deep learning approaches for AD. This is motivated by a lack of effective methods for AD tasks that involve complex data, for instance, cancer detection from multigigapixel whole-slide images in histopathology [124]. As in other adoptions of deep learning, the goal of deep AD is to mitigate the burden of manual feature engineering and to enable effective, scalable solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been a surge of interest in developing deep learning approaches for AD. This is motivated by a lack of effective methods for AD tasks that involve complex data, for instance, cancer detection from multigigapixel whole-slide images in histopathology [124]. As in other adoptions of deep learning, the goal of deep AD is to mitigate the burden of manual feature engineering and to enable effective, scalable solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Dimensionality reduction techniques are commonly used to visualize network representations of data and gain intuition into how the network separates classes, but they can also be used to identify outlier data. In ( Faust et al , 2018 ), the authors apply a k nearest neighbors approach to tSNE-produced representations of patches drawn from whole slide histology images of CNS tissue samples. They find that tSNE representations of new glioma patches fall close to glioma patches in their training data.…”
Section: Discussionmentioning
confidence: 99%
“…It can thus be used for several applications, for example visualizing patterns and clusters across classes and detecting outliers. This technique has been applied to the classification of abdominal ultrasound images ( Cheng and Malhi, 2017 ) as well as classification and anomaly detection in histopathology images ( Faust et al , 2018 ). An example of tSNE images generated from ( Faust et al , 2018 ) is shown in Figure 4A .…”
Section: Understanding Model Structure and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…A class-activation map technique was employed to provide a heat map to identify the location of the lung nodule. 58 …”
Section: Interpretability Improvement For Deep Learningmentioning
confidence: 99%